From reading difficulty to interactive-compensatory reading / Sharifah Amani Syed Abdul Rahman, Noor Hanim Rahmat and D Rohayu Mohd Yunos - Syed Abdul Rahman, Sharifah Amani; Rahmat, Noor Hanim; Mohd Yunos, D Rohayu (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
Students leaving secondary schools may need more time to adjust to the changing demand of reading activities. This is because, the types of reading in higher institutions require more effort and commitment from the readers. Readers often practice compensation strategies to aid understanding. This study was carried out to investigate the perception of learners towards academic writing by looking at what readers consider as reading difficulty. This study also attempted to look at readers’ perception and the different types of strategies in academic reading. 106 participants were randomly chosen to respond to a 5-part questionnaire and SPSS analysis is done to record the frequency of responses and presented in the form of mean scores. Findings reveal interesting implications for the teaching and learning of academic reading as readers combine the use of compensatory approaches to aid their understanding when reading academic texts.